Application of MIKE11 Model in River Network Area of Pearl River Delta for Water Quality Improvement - LI Qingfeng; GUO Shan; ZHANG Ruyu; YAN Xiaoman; ZHANG Xuelin (Renmin Zhujiang)
The water quality improvement in the river network area of the Pearl River Delta is an important part of the comprehensive management of the river basin,and it is necessary to study the compliance of water quality improvement measures.Taking the Beicun river system of Nanhai district,Foshan city in the Pearl River Delta as an example,this paper chooses COD,NH3-N and TP as the characteristic indexes based on the MIKE11 one-dimensional hydrodynamic water quality model to study the hydrodynamic force of rivers and water quality improvement effect under different engineering schemes.The results show that measures such as pollution interception,silt removal,and water diversion can improve the overall water quality of the studied river reach in varying degrees,and thus the water quality improvement is achieved.As the projects of pollution interception and fresh water are implemented,the water quality in typical cross sections of main rivers in the Beicun river system can meet the requirement of class Ⅴ.After the implementation of water diversion and transfer,as well as CSO storage pool,the pollutant concentration in the observed cross section of seriously polluted rivers decreases by more than 70%.As a result,this paper can provide a basis for improving water quality in the river network area of the Pearl River Delta.